Il Geoportale Nazionale del Ministero dell’ambiente e della Tutela del Territorio e del Mare - Costabile, Salvatore (GEOmedia, 2010)
MATTM National Geoportal The National Geoportal has been recently developed by the italian Department of the Environment and Land Protection (MATTM) and represents an asnwer to all the issues connected to a growing need of Geographic Informations. The aim of an infrastructure like the one created by MATTM is to provide an affordable base for the future planning and managing of Italy's land resources; the informations and metadata featured by the portal have been created with regard to the rules proposed by the INSPIRE Directive.